European Funds and Green Public Procurement - Ruben Nicolas; Vitĕzslav Titl; Fredo Schotanus (CESifo GmbH, 2024)
The European Commission co-funds public projects through the European Structural and Investment Funds (ESIF) to stimulate the sustainable economic development of EU Member States. The ESIF budget is about 90 billion euros annually and ESIF beneficiaries are explicitly encouraged to increase their use of Green Public Procurement (GPP) since 2014. In this paper, we study to what extent ESIF co-funding affects the uptake of GPP, using a dataset with all public tender notices in the Czech Republic (2006-2019). Our findings suggest that ESIF co-funding instigates selection behaviour by contracting authorities to improve chances of receiving co-funding. After accounting for selection effects, we find that ESIF co-funding has a small but significant effect on the uptake of GPP. Studying exogenous changes in the ESIF policy conditions, we find that GPP uptake responds to changes in the availability of co-funding and not to stronger policy objectives related to sustainability. Finally, we find that the contracting authority's prior experience with GPP is positively associated with ESIF co-funding and has only a small effect on GPP uptake aside from ESIF.
Keywords: H57; D73; 330; green public procurement; EU; co-funding; climate policy; policy evaluation; sustainable developmen